Opisthorchiasis and pancreatic cancer - V. V. Ivanov; T. B. Komkova; I. A. Lyzko; E. A. Perina; I. A. Popov; E. V. Udut; E. S. Khmelevskaya (Бюллетень сибирской медицины)
Chronic opisthorchiasis is recognized as a precancerous condition that can present similarly to other diseases of the hepatopancreatoduodenal zone. Statistically, there is a proven correlation between the duration and intensity of parasitic invasion and the development of carcinogenesis, with the manifestations of opisthorchiasis often obscuring the early symptoms of cancer. Many researchers are working to find methods for the early diagnosis of pancreatic cancer against the background of chronic opisthorchiasis, which may enable timely treatment of the disease in the early stages. The authors of this lecture present a literary review of the data on the incidence of pancreatic cancer in patients with chronic opisthorchiasis. Additionally, some factors contributing to cholangiocarcinoma carcinogenesis are discussed, since the exact mechanisms leading from the introduction of a trematode to the formation of a malignant process are multifunctional. Certain phenomena regarding the effect of opisthorchis on the human body currently lack explanation and require further study and clarification.